Learn to be nice - Abd Razak, Dzulkifli (2007)
IF racial harmony and ethnic relations could come from the introduction of an education module in a university, the world would have been at peace with itself a long time ago. Sadly, in reality, this is not the case. This is why any such expectations arising from the recently approved module on ethnic relations for public universities should be treated with caution. The module’s chief editor remarked that the new module "won’t provide quick solutions". This seems to be a realistic assessment. The module, which has undergone redrafting six times before being given the seal of approval by the Cabinet, goes to show how gingerly racial and ethnic issues are handled. Though racial sensitivities are not peculiar only to our country, Malaysians seems to be more pre-occupied by it, given its very diverse background and makeup.